1986
DOI: 10.1007/bf02377153
|View full text |Cite
|
Sign up to set email alerts
|

Influence of neem leaf on nitrification in a lowland rice soil

Abstract: Summary Application of neem products like neem leaf and neem cake to wetland soil did not have any adverse effect on the population of heterotrophic microflora; nitrifying bacteria, on the other hand, decreased significantly due to addition of neem cake and fresh and dried neem leaf with urea. It is suggested that neem leaf could be used as an inhibitor of nitrification for enhancing nitrogen use efficiency of fertilizers where neem leaf is available in plentiful supply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 3 publications
1
4
0
1
Order By: Relevance
“…Studies conducted by Patel and Desai (1985) also gave similar observations with organophosphorus pesticides. Neem oil cake showed significant suppression of both the chemoautotrophs which is in agreement with the observations of Mishra et al, (1975), Santhi et al, (1986) and Gopal (1995). It is also a well known fact that neem extracts are being used with urea prills as nitrification retarders (Waghray, 1997).…”
Section: Discussionsupporting
confidence: 91%
“…Studies conducted by Patel and Desai (1985) also gave similar observations with organophosphorus pesticides. Neem oil cake showed significant suppression of both the chemoautotrophs which is in agreement with the observations of Mishra et al, (1975), Santhi et al, (1986) and Gopal (1995). It is also a well known fact that neem extracts are being used with urea prills as nitrification retarders (Waghray, 1997).…”
Section: Discussionsupporting
confidence: 91%
“…This implies the presence of an easily mineralizable N pool in the manure usually related to less stable organic matter (Laos, Satti, Walter, & Mazzarino, 2000;Preusch, Adler, Sikora, & Tworkoski, 2002). T1 T2 T5 T8 T10 T13 Neem acting as a nitrification inhibitor when mixed with inorganic fertilizers was widely reported (Santhi et al, 1986;Suganya et al, 2007;Gnanavelrajah, 2011). In the present study it was observed that the NO 3 2-N content remains significantly lower than the control in VC + Neem treatment during the initial 10 days indicating that nitrification has been inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Após secas ao ar, destorroadas e passadas em peneira de malha de 2,0 mm, as amostras foram encaminhadas ao Laboratório de Solos e Nutrição Mineral do CCTA/UFCG para sua caracterização química e física (Tabela 1) conforme procedimentos descritos em EMBRAPA (2011). O preparo dos extratos e sua aplicação no solo foi baseada em (Santhi et al, 1986 No preparo das soluções de ureia foram tomados 100 mL de cada extrato (correspondente a 1,0 g de matéria seca de folhas ou de sementes) nos quais foram adicionados ureia nas proporções de 10,0 g; 5,0 g; 3,3 g e 2,5 g 100 mL -1 , obtendo-se as proporções de 10, 20, 30 e 40%, respectivamente. Na proporção 0%, foi tomado 50 mL de álcool mais 50 mL de água destilada e adicionado 10 g de ureia.…”
Section: Methodsunclassified